2007
DOI: 10.1002/ppap.200700096
|View full text |Cite
|
Sign up to set email alerts
|

Creation and Recombination of Free Radicals in Fluorocarbon Plasma Polymers: An Electron Spin Resonance Study

Abstract: Generation and recombination processes of plasma‐induced radicals in plasma polymers are investigated using ESR, which provides valuable information about radicals in thin polymer films. The polymer films are prepared by means of r.f. plasma polymerization of c‐C4F8. Radical numbers and densities of fluorocarbon plasma polymer coatings of different thicknesses are measured by extrapolating mixed‐order recombination processes. The kinetics of radical generation in plasma polymer films is modeled using the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 33 publications
1
28
1
1
Order By: Relevance
“…Unlike Parylene, which was found to have no detectable electron‐spin resonance (ESR) signal,28 plasma polymers are known to be extremely rich in trapped free radicals 29, 30. These can react over time with oxygen from the atmosphere, as portrayed in Equation (5).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike Parylene, which was found to have no detectable electron‐spin resonance (ESR) signal,28 plasma polymers are known to be extremely rich in trapped free radicals 29, 30. These can react over time with oxygen from the atmosphere, as portrayed in Equation (5).…”
Section: Resultsmentioning
confidence: 99%
“…However, the concentration of middle-sized fragments in the active volume of the discharge during plasma deposition of AMA (C 3 H 5 þ and C 4 H 5 O þ ) and PiB (C 3 H 7 þ and C 4 H 7 O þ ) both tended to decrease. In literature, the chemical analysis of thin plasma films based on FTIR, XPS, [15,16] solid state 13 C NMR, [17] optical emission spectroscopy (OES), [18] electron spin resonance spectroscopy (ESR), [19,20] mass spectrometry, [21] and secondary ion mass spectroscopy (SIMS) [22][23][24] is predominant.…”
Section: Introductionmentioning
confidence: 99%
“…After assessing the properties of plasma films produced at atmospheric pressure, it was clear that these coatings show some significant shortcomings compared to their analogues produced by conventional polymerization. In general, it has been shown that plasma polymerized materials contain unsaturations, and a large number of trapped radicals . This results in the fact that AP plasma coatings are prone to post plasma reactions, in contrast with their assumed chemical inertness.…”
Section: Introductionmentioning
confidence: 99%